Risk management strategies for the 2022 Olympic Winter Games: The Beijing scheme - Liu, J.; Lou, J.; Wang, Y.; Zhang, J. (Journal of Sport and Health Science, 2022)
As the first international sporting event scheduled since the outbreak of the novel coronavirus disease 2019 (COVID-19) pandemic, the Beijing XXIV Olympic Winter Games were officially held in China between the 4th and 20th of February 2022.1 According to the International Olympic Committee (IOC), there were approximately 2900 elite athletes from 91 National Olympic Committees competing in 109 events during the 16 days of the Games.2 In fact, under the conditions of a global pandemic, mass gatherings during large-scale sporting events represent a conducive environment for viral transmission given the close, prolonged, and frequent interactions between participants; this includes an increased risk of transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). These conditions pose considerable public health challenges for the competition organizers and local governments. It was of paramount importance to develop detailed risk management measures and technical recommendations tailored to different events and scenarios to ensure the safety of all involved in the Olympic Games.